TEACHING THE FUNDAMENTALS OF PEDAGOGICAL COMMUNICATION VILLAGE IN HIGH SCHOOL - V.V. Pochuyeva (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the problem of training in basics of pedagogical communication at USA higher colleges as a factor of professional development of the future specialist by means of training in intensive communication groups, creating laboratories of pedagogical guidance and pedagogical tutorship.